(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The authors describe the recent advances in agricultural acarology and briefly examine the principal research lines that have been involving during the last years various researchers. In particular, the use of informatic application and mathematical models in crop protection against phytophagous mites, the population dynamics, the behaviour of preys and predators, the population genetics and also the molecular biology are discussed.